2018
DOI: 10.1016/j.ihj.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of essential hypertension in young adult males followed for over two decades

Abstract: BackgroundThe data about the incidence of hypertension in India is scarce and is lacking about hypertension in young adult patients. We studied the incidence of hypertension in a cohort of young adult male military personnel followed for a long duration.MethodsThe data for this retrospective, observational study was derived from the electronic medical records (EMR) of the male service personnel enrolled between 1990 and 2015. All subjects were recruited before 18 years of age in good health without any disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Such estimates are now feasible within programmatic settings, with implementation of annual blood pressure screening in all adults. [30] 52217 12.7 years 17 years +…”
Section: Discussionmentioning
confidence: 99%
“…Such estimates are now feasible within programmatic settings, with implementation of annual blood pressure screening in all adults. [30] 52217 12.7 years 17 years +…”
Section: Discussionmentioning
confidence: 99%
“… 5 As to incidence, rates have been reported of 58.6 cases per 100 000 people (95% CI 52.8 to 64.9) in young adults (median age 33 years). 6 …”
Section: Introductionmentioning
confidence: 99%
“…5 As to incidence, rates have been reported of 58.6 cases per 100 000 people (95% CI 52.8 to 64.9) in young adults (median age 33 years). 6 According to WHO, hypertension increases the risk of coronary heart disease by three to four times, and the risk of cardiovascular disease by two to three times. 7 In this regard, a study of the Global Burden of Hypertension and Systolic Blood Pressure of at least 110-115 mm Hg between 1990 and 2015, reported that most of the SBP-related deaths were caused by ischaemic cardiopathy (54.5%), haemorrhagic stroke (58.3%) and ischaemic stroke (50,0%).…”
mentioning
confidence: 99%